2017
DOI: 10.1080/03007995.2017.1360850
|View full text |Cite
|
Sign up to set email alerts
|

Real-world costs and outcomes in metastatic renal cell carcinoma patients treated with targeted therapies: a cohort study from the French health insurance database

Abstract: This descriptive study showed that the economic burden of mRCC is substantial with oral targeted therapies accounting for 53% of the PPPM. OS and PFS in real life are poorer than observed in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
1
18
2
Order By: Relevance
“…The most expensive treatment period in the present study was the active period during first-line treatment, driven by high outpatient pharmacy expenditures. These costs are considerably higher than data from France reporting overall healthcare costs of €5,546.0/month during first-line treatment, compared with €7,253.2/month observed in the current study [17]. Similar to the current findings, the driver of the costs in the French study was outpatient pharmacy expenditures, accounting for 53% of the overall monthly costs in France [17].…”
Section: Discussionsupporting
confidence: 74%
“…The most expensive treatment period in the present study was the active period during first-line treatment, driven by high outpatient pharmacy expenditures. These costs are considerably higher than data from France reporting overall healthcare costs of €5,546.0/month during first-line treatment, compared with €7,253.2/month observed in the current study [17]. Similar to the current findings, the driver of the costs in the French study was outpatient pharmacy expenditures, accounting for 53% of the overall monthly costs in France [17].…”
Section: Discussionsupporting
confidence: 74%
“…Our findings that TKIs accounted for the most frequently used first-line treatment in Germany are, in general, consistent with the results of previously published retrospective observational studies from other countries. [26][27][28][29] We also present the treatment reality of recent years, whereas existing literature has often covered a shorter observation period than ours. 26,28,30,31 Over time, our data show a decline of sunitinib treatment in favor of pazopanib, following European marketing approval.…”
Section: Discussionmentioning
confidence: 98%
“…[26][27][28][29] We also present the treatment reality of recent years, whereas existing literature has often covered a shorter observation period than ours. 26,28,30,31 Over time, our data show a decline of sunitinib treatment in favor of pazopanib, following European marketing approval. The British RECCORD (Renal Cell Carcinoma Outcomes Research Dataset) registry also reported a shift from sunitinib to pazopanib between 2009 and 2012, with sunitinib remaining the most common first-line treatment.…”
Section: Discussionmentioning
confidence: 98%
“…RWD studies used a variety of sources to extract data, including national and local cancer registries, insurance databases, pharmacy databases, and patient medical records [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Studies were from a wide range of countries, including USA, Canada, Australia, Spain, France, Greece, Italy, Netherlands, Czech Republic, China, Japan, Korea, and India.…”
Section: Systematic Reviewmentioning
confidence: 99%